LANDSLIDE GEOHAZARD FOR PIPELINES OF NATURAL GAS TRANSPORT - Marinos, V.; Stoumpos, G.; Papathanassiou, G.; Grendas, N.; Papouli, D.; Papazachos, C. (Bulletin of the Geological Society of Greece, 2016)
Landslides represent a significant hazard for pipelines because they can generate permanent ground displacement and tend to result in complete failure or significant leaks, major environmental impacts and long periods of service disruption. Hence, landslide-related incidents are regarded as a significant operational risk. The paper mainly focuses on the assessment of landslide hazard along or across a natural gas pipeline project and on the identification of these hazards, mostly in the field. Whether the “expected” landslide event reaches the Right of Way (RoW) and impacts the pipeline, is influenced by the nature and size of the expected landslide event, controlled by the site geology and geomorphology, the proximity of the existing landslide feature to the pipeline and the position of the pipeline relative to the landslide. Landslide hazard assessment is used to identify “hot spots” along the pipeline route where re-routing or risk reduction measures must be prioritised. When landslides that can threat the pipeline integrity cannot be avoided, more detailed site evaluation is required to support the design and construction of mitigation measures.